1986
DOI: 10.1063/1.337554
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of interelectrode flashover in air with the existence of a weakly ionized plasma channel induced by a KrF laser (248 nm)

Abstract: The irradiation of a KrF laser (248 nm) into the interelectrode space affects the electric flashover characteristics there. The results obtained show that negative oxygen ions dominate formation of the interelectrode arc in air. A laser beam is introduced parallel to the interelectrode axis and the equipment is arranged to prevent the occurrence of photoelectric effects on the electrode surfaces. The time separation between laser firing and application of the interelectrode voltage is varied from 10 ns to 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Thus, we consider that the electrons do not play an important role. Sasaki et al 10 have already reported the similar results and pointed out the importance of the negative ions. Since time to flashover and guide length of the laser-guided positive discharge do not change drastically from the delay time of Ϫ1 s to that of 10 s, we considered that the mechanisms of the triggering and guiding ability at the negative delay times are fundamentally similar to those at the positive delay times.…”
Section: B Positive Polaritysupporting
confidence: 54%
See 1 more Smart Citation
“…Thus, we consider that the electrons do not play an important role. Sasaki et al 10 have already reported the similar results and pointed out the importance of the negative ions. Since time to flashover and guide length of the laser-guided positive discharge do not change drastically from the delay time of Ϫ1 s to that of 10 s, we considered that the mechanisms of the triggering and guiding ability at the negative delay times are fundamentally similar to those at the positive delay times.…”
Section: B Positive Polaritysupporting
confidence: 54%
“…There have been several experiments on laser-guided discharges using ultraviolet lasers. 10 But most were conducted under low pressure. 11,12 We attempted to guide the discharge in atmospheric air using a KrF laser ͑248 nm͒ with a pulse energy of 750 mJ.…”
Section: Introductionmentioning
confidence: 99%
“…However, in these researches, the laser intensity is very high. For example, the laser intensity should be higher than 10 11 W/cm 2 when infrared (1.06 μm) is used in laser-triggered lightning discharge [52], and should be higher than 10 8 W/ cm 2 for UV laser (248 nm) [53]. As mentioned earlier, at such a strong beam intensity, MPI and inverse Bremsstrahlung will occur.…”
Section: Discussion and Analysismentioning
confidence: 97%
“…Generally, it is difficult to measure plasma and the electrons in the plasma simultaneously. Therefore, we attempted to perform an electrical investigation of the behavior of electrons that are synchronized with PLPP using a symmetric double probe (SDP) [5]. The conventional double-probe method such as the one that is reported in floating-probe experiments [17] is not suitable for after-glow plasmas because, in our experiment, PLPP localizes in the SDP gap without coming in contact with the electrode surfaces.…”
Section: Introductionmentioning
confidence: 98%